Persepsi Penggunaan Black Box.AI Sebagai Media Pembelajaran Era Digital pada Mahasiswa Institut Az Zuhra Angkatan 2024 - Noprieka Suriadiman (Pusat Riset dan Inovasi Nasional, 2026)
This study examines students’ perceptions of the use of Black Box.AI as a digital learning medium in the era of technological advancement. The rapid development of digital technology, particularly artificial intelligence, has significantly transformed learning practices in higher education, encouraging students to adopt more flexible and independent learning strategies. This research aims to analyze how students perceive the usefulness, effectiveness, and challenges of using Black Box.AI in supporting their academic activities. A qualitative descriptive approach was employed, with data collected through observations, interviews, and documentation involving four students from Institut Az Zuhra who actively use the platform. The findings reveal that students generally have positive perceptions of Black Box.AI, as it is considered practical, efficient, and capable of providing fast and concise information. The platform is particularly helpful in simplifying complex or technical materials, assisting students in completing assignments, and supporting self-directed learning. However, the study also identifies several challenges, including initial confusion in navigating certain features, dependency risks, and the need for lecturer validation to ensure the accuracy of information. The results indicate that while Black Box.AI plays a significant role as a supporting learning tool, it does not replace the role of educators. The study implies that the integration of artificial intelligence in education should be accompanied by critical thinking skills and proper guidance to optimize learning outcomes and maintain academic integrity..